Organic Phosphorus in the Environment - Turner, BL; Baldwin, D.; Frossard, E.; Ebooks Corporation (Wallingford : CABI, 2005)
Organic phosphorus is involved in almost every biological process and is essential for life. However, the role of organic phosphorus and mechanisms for its dynamics has been poorly understood.
Contenido: 7. Microbial Turnover of Phosphorus in Soil8. Utilization of Soil Organic Phosphorus by Higher Plants; 9. Microbial Turnover of Organic Phosphorus in Aquatic Systems; 10. Ecological Aspects of Phosphatase Activity in Cyanobacteria, Eukaryotic Algae and Bryophytes; 11. Organic Phosphorus Dynamics in Tropical Agroecosystems; 12. Organic Phosphorus Transfer from
Libro electronico adquirido a perpetuidad con la editorial CABI
Keywords: SUELOS -- CONGRESOS, CONFERENCIAS ETC. -- CONTENIDO DE FOSFORO